Review and analysis of the effectiveness of the multidisciplinary model for diabetes care. - Escobar-Trinidad, Joaquín Arnoldo; Arredondo-López, Abel Armando (Horizonte Sanitario, 2019)
Objective: To describe the effectiveness of the multidisciplinary model of care in the treatment of people with type II diabetes. Material and Method: Based on a literary search using the google academic search engine for the ease in its use, studies were searched that will involve the subject of interest multidisciplinary models in the treatment of Diabetes. A narrative synthesis was carried out that was carried out from the studies that were found, which consisted in a summary of each study that included the country of the study, description of the methodology, the size of the sample, and a synopsis of the results. Results: The analyzed studies were classified according to their score in the categories: changes of biochemical markers, prevention and reduction of adverse events and cost-effectiveness analysis. In all the categories of analysis, the evidence was broadly favorable in patients with multidisciplinary management. Conclusions: Multidisciplinary group care in patients with diabetes has significant advantages with respect to purely biomedical care. It offers the emotional and social support of people with similar experiences and serves as a model of greater resolution of the problem to patients in similar circumstances, favoring the ability to achieve diabetes management goals. Keywords: Patient Care Team; Diabetes Mellitus Type 2; Cost-Effectiveness Evaluation.